Venture capital investments - Kumar, Raj; Sharma, Manu (New Delhi SAGE Publications India Pvt Ltd, 2020)
"Venture Capital is a form of financing provided by wealthy investors, investment banks and other financial institutions to start-ups and small to medium-sized enterprises with strong growth potential in exchange of private equity stakes. These investors are also known as venture capitalists (VCs). With the rise of start-ups and small ventures, the market of VCs and the interest of people in venture capitalism are also increasing. The valuation of the firms done by the VCs at the beginning stage is not just a betting game. It is thorough research done using different strategies and computing formulas. This book gives a fundamental understanding of various aspects of venture capital covering the nature of investments, deal evaluation, valuation, structure, economics and fundraising. It begins by covering how the private market is different from the public market. The history of venture capital is discussed with the venture capital industry in the background. The authors also discuss the deal of valuation, valuation and fundraising from the perspective of a VC. Finally, the book discusses fund economics and fund structure in venture capital firms. It provides challenges a VC faces right from raising funds to evaluating a potential deal, deal evaluation and exit evaluation . The book will be a helpful read for entrepreneurs who want to get into the shoes of a VC and understand how they valuate a firm or a start-up. It will also be an informative read for the aspiring VC who is looking to enter the venture capital market"--
Includes bibliographical references.
Keywords: Kumar Raj; Venture capital; Capital investments